Sulle tracce dei rescripta richiesti da privati nella tarda antichità - Mantovani, Dario (Tesserae iuris, 2023)
Uncertainties regarding the fate and role of rescripts addressed by emperors in response to petitions of individuals in Late Antiquity depend primarily on the lack of a complete and updated inventory. Firstly, a content-based typology is presented, which highlights the persistence of rescripts intended to solve interpretative questions of private and criminal law. Then, an overview of the main sources – literary, epigraphic, papyrological – and of the already extant (partial) lists and inventories of rescripts (or of petitions) is outlined. This survey shows that, from Constantine to Justinian, a large amount of “private” rescripts continued to be issued.